Vat photopolymerization of multifunctional fresnel lenses for ocular management - Ali, Murad; Hisham, Muhammed; Abu Al-Rub, Rashid K.; Butt, Haider (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, multifunctional Fresnel lenses were explored as a potential solution for correcting vision in patients with color vision deficiency (CVD) and high myopia. Current studies have primarily focused on color vision correction through the 3D printing of glasses and contact lenses. However, the potential of 3D-printed multifunctional devices, such as Fresnel lenses, goes beyond addressing a single vision correction issue. For this study, computer-aided design (CAD) model of Fresnel lens with high diopter based on constant height configuration was developed. The CAD model was successfully fabricated using vat photopolymerization 3D printer, employing laboratory-prepared transparent HEMA resin. The resin was modified with two Atto dyes (565 nm and 488 nm), known for their ability to filter out problematic wavelengths (400–500 nm and 540–580 nm) to address color vision deficiency. The printed lenses were characterized by their chemical, physical, and optical properties using various characterization techniques. The focusing performance was evaluated using focal length measurements, and the results obtained were less than 2 mm deviation from the design value, having the potential to assist in higher myopic vision correction. The resulting optical spectra were compared with commercial glasses, revealing close agreement for CVD correction. These results expand the potential applications of multifunctional Fresnel lenses in ophthalmology, demonstrating their effectiveness as vision-correcting lenses and imaging systems.